A quinazoline derivative suppresses B cell hyper-activation and ameliorates the severity of systemic lupus erythematosus in mice - Zhang, Gan; Yang, Fan; Li, Juan; Chen, Shan; Kong, Yuhang; Mo, Chunfen; Leng, Xiao; Liu, Yang; Xu, Ying; Wang, Yantang (Frontiers in Pharmacology, 2023)
Background: Aberrant autoreactive B cell responses contribute to the pathogenesis of systemic lupus erythematosus (SLE). Currently, there is no safe and effective drug for intervention of SLE. Quinazoline derivative (N4-(4-phenoxyphenethyl)quinazoline-4,6-diamine, QNZ) is a NF-κB inhibitor and has potent anti-inflammatory activity. However, it is unclear whether QNZ treatment can modulate B cell activation and SLE severity. Methods: Splenic CD19+ B cells were treated with QNZ (2, 10, or 50 nM) or paeoniflorin (200 μM, a positive control), and their activation and antigen presentation function-related molecule expression were examined by flow cytometry. MRL/lpr lupus-prone mice were randomized and treated intraperitoneally with vehicle alone, 0.2 mg/kg/d QNZ or 1 mg/kg/d FK-506 (tacrolimus, a positive control) for 8 weeks. Their body weights and clinical symptoms were measured and the frequency of different subsets of splenic and lymph node activated B cells were quantified by flow cytometry. The degrees of kidney inflammation and glycogen deposition were examined by hematoxylin and eosin (H&E) and PAS staining. The levels of serum autoantibodies and renal IgG, complement C3 deposition were examined by ELISA and immunofluorescence. Results: QNZ treatment significantly inhibited the activation and antigen presentation-related molecule expression of B cells in vitro. Similarly, treatment with QNZ significantly mitigated the SLE activity by reducing the frequency of activated B cells and plasma cells in MRL/lpr mice. Conclusions: QNZ treatment ameliorated the severity of SLE in MRL/lpr mice, which may be associated with inhibiting B cell activation, and plasma cell formation. QNZ may be an excellent candidate for the treatment of SLE and other autoimmune diseases.